2009
DOI: 10.1007/978-3-540-79088-4_2
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Physiological Aspects of Endogenous Androgens

Abstract: This review attempts to give a synopsis of the major aspects concerning the biochemistry of endogenous androgens, supplemented with several facets of physiology, particularly with respect to testosterone. Testosterone continues to be the most common adverse finding declared by World Anti-Doping Agency accredited laboratories, such samples having an augmented testosterone to epitestosterone ratio. Knowledge regarding the precursors and metabolism of endogenous testosterone is therefore fundamental to understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 175 publications
0
24
0
Order By: Relevance
“…This effect was ascribed to the inhibition of the 17a-hydroxylase and 17, 20-lyase activities of CYPC17 (conversion of pregnenolone to DHEA and progesterone to ASD) [40], but recent studies have also shown its inhibitory potential on steroid glucuronidation in vitro [13,16]. Figure 1 schematizes androgen biosynthetic and excretion metabolic pathways and underlines the sites of metabolic modulations by ketoconazole and finasteride [41].…”
Section: Introductionmentioning
confidence: 95%
“…This effect was ascribed to the inhibition of the 17a-hydroxylase and 17, 20-lyase activities of CYPC17 (conversion of pregnenolone to DHEA and progesterone to ASD) [40], but recent studies have also shown its inhibitory potential on steroid glucuronidation in vitro [13,16]. Figure 1 schematizes androgen biosynthetic and excretion metabolic pathways and underlines the sites of metabolic modulations by ketoconazole and finasteride [41].…”
Section: Introductionmentioning
confidence: 95%
“…T has been clearly linked to behavior and sexual function in men (7,35), with influence on sexual desire, sexual thoughts, the intensity of sexual feelings, and sexual activity (36,37). Studies using animal models have also described a decrease in T concentration and a higher frequency of erections in sleep-deprived rats (8)(9)(10).…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, by supplementing old rats with ‘new’ testosterone, more bioavailable (free) testosterone may have been produced in the circulation. Additionally, as high androgen levels are known to decrease SHBG (Plymate et al 1983; Selby, 1990; Kicman, 2010), abruptly raising serum testosterone levels may have also resulted in a greater local proportion of bioavailable testosterone that contributed to the restoration of XII LTF and enhancement of phrenic LTF.…”
Section: Discussionmentioning
confidence: 99%